2013
DOI: 10.1088/0967-3334/34/8/n63
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validation of Xsens MVN measurement of lower limb joint angular kinematics

Abstract: This study aims to validate a commercially available inertial sensor based motion capture system, Xsens MVN BIOMECH using its native protocols, against a camera-based motion capture system for the measurement of joint angular kinematics. Performance was evaluated by comparing waveform similarity using range of motion, mean error and a new formulation of the coefficient of multiple correlation (CMC). Three dimensional joint angles of the lower limbs were determined for ten healthy subjects while they performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
224
2
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(245 citation statements)
references
References 13 publications
11
224
2
8
Order By: Relevance
“…Basic step counting does not provide sufficient detail for understanding the quality of a patients mobility, thus more detailed metrics such as step time, stride time variability and step distance are required. Very detailed gait metrics include kinetic and kinematic measures which are obtained in biomechanics labs, or else remotely through the use of an inertial measurement unit (IMU) on each body segment [6], such systems are beyond the scope of this work. Three of the most commonly used IMU mounting locations to obtain quality of gait metrics in the literature include, an IMU over the spine on the lower back, two IMUs on the lower legs or two IMUs on the dorsal aspect of each foot.…”
Section: Introductionmentioning
confidence: 99%
“…Basic step counting does not provide sufficient detail for understanding the quality of a patients mobility, thus more detailed metrics such as step time, stride time variability and step distance are required. Very detailed gait metrics include kinetic and kinematic measures which are obtained in biomechanics labs, or else remotely through the use of an inertial measurement unit (IMU) on each body segment [6], such systems are beyond the scope of this work. Three of the most commonly used IMU mounting locations to obtain quality of gait metrics in the literature include, an IMU over the spine on the lower back, two IMUs on the lower legs or two IMUs on the dorsal aspect of each foot.…”
Section: Introductionmentioning
confidence: 99%
“…GT3X was included as standard measurements for step count since it is the most commonly used activity monitor for analyzing ambulation in healthy and diseased populations, including MS [24]. MTx served as a reference standard for assessing temporal gait parameters as its accuracy to measure these has been validated [25,34].…”
Section: Swing Timeðiþ ¼ To Left ðIþ à Hs Left ðIþ ð2þmentioning
confidence: 99%
“…Also, the study did not include gold-standard for estimating the true outcomes for temporal gait parameters. However, previous studies have been found that the accuracy of MTx in measuring gait is valid when compared to the gold standards (motion capture system, pressure sensor switches) [25,34]. Lastly, gait speed was utilized to distinguish gait impairment levels of PwMS since it has been reported as an objective spatiotemporal measure of gait impairment [51].…”
Section: Strengths and Limitations Of The Investigationmentioning
confidence: 99%
“…Despite the high precision [18][19][20], IMUs have only been used so far to quantify and characterize movement patterns and effects of interventions in post-stroke patients [19][20][21], with only anecdotal evidence of their use in rehabilitation tools [22][23][24].…”
Section: Introductionmentioning
confidence: 99%